The effects of task modality on L2 Chinese learners' pragmatic development: Computer-mediated written chat vs. face-to-face oral chat. (February 2019) - Tang, Xiaofei
Abstract: Recent studies in Task-based Language Teaching showed the unique benefits of computer-mediated communication (CMC) on task-based interaction such as providing visual saliency of text and extended processing time for modified output (e.g., Smith, 2004, 2005). However, it is not clear whether CMC is more conducive for task-based learning compared to traditional face-to-face (FTF) mode. This study directly compared the effects of the two task modalities (CMC and FTF) on the pragmatics learning of Chinese modal verbs. This study focused on task-based pragmatics learning because tasks are supposed to promote learners to use language for pragmatic purposes. Thirty learners of L2 Chinese (high-elementary to intermediate level) completed two decision-making tasks in pairs. Half of the participants completed the tasks in CMC (N = 16), while the other half completed the same tasks in FTF (N = 14). Production and recognition tests were used at pre, post and delayed post-test to measure the learning outcomes. Task-based interaction in both modalities was analyzed for the frequency and pattern of modal verb use. Resudlts showed that the FTF group outperformed the CMC group at the immediate and delayed post-test. The FTF group also produced modal verbs more frequently during the tasks. Contrary to the previous claims on the potential advantages of CMC, this study indicates that FTF might be more beneficial for task-based pragmatics learning. The efficacy and challenges of CMC-based learning thus deserves further investigation.